AI Rice Selection: Deconstructing Signs and Myths of Rice Comedy Ads on Instagram @alameen.had - Azzahra, Arina Zakiah; Mustofa, Arif (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2025)
Increasingly competitive business competition has encouraged manufacturers to innovate in promoting their products, one of which is through audiovisual advertising media. However, most previous studies have only highlighted the persuasive aspect without exploring the symbolic meaning contained therein. Therefore, this study was conducted to reveal the hidden signs and meanings in rice comedy advertisements on the Instagram account @alamee.had, focusing on the mythology of AI sophistication and validity based on Roland Barthes' perspective. This study used a qualitative method with Roland Barthes' semiotic approach, which includes denotative, connotative, and mythical analysis. Three advertising clips showing the role of AI in determining product choices were then analyzed using descriptive interpretive techniques. The results of the study show that these advertisements implicitly construct a myth about AI as a technology that is considered intelligent, rational, and has great potential to influence human decisions regarding technology in everyday life. This research theoretically expands Barthes' semiotic study through the reading of modern technology myths in contemporary Arabic advertisements.Keywords - Advertisement, AI Myths, Semiotics.